Export behaviour of SMEs in the Swedish computer service industry - Martin Falk; Eva Hagsten (Kiel Institute for the World Economy (IfW), 2015)
Export participation of SMEs in Swedish computer services has increased rapidly over the last decade. Despite the increase, export participation rates of SMEs including micro enterprises remain rather low at 13 percent in 2010. Based on uniquely linked firm-level datasets with full coverage of micro enterprises and sole proprietors, this study investigates the determinants of export participation of Swedish SMEs in the computer service industry. Exports include both goods and services. Estimates based on the conditional logit model show a significantly positive relationship between initial labour productivity and the decision to export. An interesting and new finding is that the magnitude of the relationship between the probability to export and initial labour productivity is low once firm effects are controlled for. Surprisingly, the impact of labour productivity on exporting does not differ between micro enterprises and the remaining SMEs (10-249 employees). Furthermore, skill intensity is significantly related to the probability of exporting with low marginal effects. Overall, labour productivity and skill intensity only explain a small proportion of the export boom of Swedish software SMEs.
Keywords: F14; 330; exports; productivity; computer service industry; human capital; conditional logit model